ผลของการจัดกิจกรรมการเรียนรู้สังคมศึกษาโดยใช้ปัญหาเป็นฐานที่มีต่อความสามารถในการแก้ปัญหาและความรับผิดชอบต่อสังคมของนักเรียนมัธยมศึกษาปีที่ 5 EFFECTS OF ORGANIZING PROBLEM-BASED LEARNING ACTIVITIES IN SOCIAL STUDIES SUBJECT ON PROBLEM SOLVING ABILITIES - จันทรา กนก; อิศรางกูร ณ อยุธยา วลัย (An Online Journal of Education, 2014)
การวิจัยครั้งนี้เพื่อศึกษาความสามารถในการแก้ปัญหา และความรับผิดชอบต่อสังคมของนักเรียนมัธยมศึกษาปีที่ 5 ที่เรียนจากกิจกรรมการเรียนรู้สังคมศึกษาตามแนวคิดการใช้ปัญหาเป็นฐาน กลุ่มตัวอย่างที่ใช้ในการวิจัยเป็นนักเรียนชั้นมัธยมศึกษาปีที่ 5 ภาคเรียนที่ 2 ปีการศึกษา 2556 โรงเรียนสาธิตจุฬาลงกรณ์มหาวิทยาลัย ฝ่ายมัธยม จำนวน 2 ห้องเรียน รวมทั้งหมด 49 คน แบ่งเป็น 2 กลุ่ม คือ กลุ่มทดลองจำนวน 25 คน และกลุ่มควบคุมจำนวน 24 คน เครื่องมือที่ใช้ในการทดลอง คือ แผนการจัดกิจกรรมการเรียนรู้สังคมศึกษาโดยใช้ปัญหาเป็นฐาน และแผนการจัดกิจกรรมการเรียนรู้สังคมศึกษาแบบปกติ ใช้เวลาในการทดลอง 17 สัปดาห์ สัปดาห์ละ 1 คาบ คาบละ 50 นาที เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูล คือ แบบวัดความสามารถในการแก้ปัญหาซึ่งมีค่าความเที่ยงเท่ากับ 0.818 และแบบวัดพฤติกรรมความรับผิดชอบต่อสังคม เปรียบเทียบผลการวิเคราะห์ข้อมูลด้วยสถิติทดสอบค่าที (t-test) ผลการวิจัย พบว่า 1) นักเรียนที่ได้รับการจัดกิจกรรมการเรียนรู้สังคมศึกษาโดยใช้ปัญหาเป็นฐาน มีความสามารถในการแก้ปัญหา หลังเรียนสูงกว่าก่อนเรียนอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 2) นักเรียนที่ได้รับการจัดกิจกรรมการเรียนรู้สังคมศึกษาโดยใช้ปัญหาเป็นฐานมีความสามารถในการแก้ปัญหา สูงกว่านักเรียนที่ได้รับการจัดกิจกรรมการเรียนรู้สังคมศึกษาแบบปกติอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 3) นักเรียนที่ได้รับการจัดกิจกรรมการเรียนรู้สังคมศึกษาโดยใช้ปัญหาเป็นฐานมีความรับผิดชอบต่อสังคมหลังเรียนสูงกว่าก่อนเรียนอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 4) นักเรียนที่ได้รับการจัดกิจกรรมการเรียนรู้สังคมศึกษาโดยใช้ปัญหาเป็นฐานมีความรับผิดชอบต่อสังคมสูงกว่านักเรียนที่ได้รับการจัดกิจกรรมการเรียนรู้สังคมศึกษาแบบปกติอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 The purposes of this research were to study the problem solving abilities and sense of social responsibility of eleventh grade students who studied social studies through problem-based learning activities. The participants were forty-nine eleventh grade students from the Chulalongkorn University Demonstration School who were divided into two groups: an experimental group (n=25) and control group (n=24). Two sets of lesson plans based on problem-based learning activities versus conventional learning activities were used as the experimental instrument. The instruments used to collect data were a problem solving abilities test with the reliability of 0.818 and a social responsibilities test. The duration of study was seventeen weeks in which students received instruction for one period per week of fifty minutes length each. The data were analyzed with a t-test. The results of the research are as follows: 1) The students who studied social studies using problem-based learning activities had higher post-experiment problem solving abilities scores than pre-experiment scores at the .05 level of significance. 2) Students who studied social studies through problem-based learning activities had higher problem solving abilities scores than those who studied through conventional learning activities at the .05 level of significance. 3) Students who studied social studies through problem-based learning activities had higher post-experiment social responsibility scores than pre-experiment scores at the .05 level of significance. 4) Students who studied social studies with problem-based learning activities had higher social responsibility scores than those who studied with conventional learning activities at the .05 level of significance.